Relationship of Mother Characteristics, Support Support and The Role of The Bidan With Mother's Participation Following The Pregnant Woman Class - Media Fitri; Joserizal Serudji; Husna Yetti (Journal of Midwifery, 2018)
Pregnant women classes are a group of co-learning that aims to increase maternal knowledge and skills about pregnancy, pregnancy care, childbirth, postnatal care, newborn care, myths and infectious diseases and birth certificates. The implementation of the pregnant mother class program has been going on for a long time but the results of preliminary studies conducted at the Guguak Puskesmas Panjang are only a few who attend classes for pregnant women.This study aims to determine whether there was a relationship between maternal characteristics, husband support and the role of midwives with the participation of mothers following the class of pregnant women. The location of the research was conducted at Puskesmas Guguak Panjang with 74 samples. Data analysis included univariate, bivariate and multivariate analysis.The results of the bivariate analysis showed that there was no correlation between maternal characteristics with maternal participation in maternal class while emotional support, instrumental support, information support and assessment support (p = 0.0001) had a relationship with maternal participation in the class of pregnant women. The role of external midwives (p = 0.002), the role of internal midwives (p = 0.001) related to maternal participation in the mother's class. Multivariate results show the role of internal midwives that greatly influences the participation of mothers who attend classes for pregnant women (p = 0.001).The role of midwives and husband support greatly affects the participation of mothers following the class of pregnant women.Pregnant women classes are a group of co-learning that aims to increase maternal knowledge and skills about pregnancy, pregnancy care, childbirth, postnatal care, newborn care, myths and infectious diseases and birth certificates. The implementation of the pregnant mother class program has been going on for a long time but the results of preliminary studies conducted at the Guguak Puskesmas Panjang are only a few who attend classes for pregnant women.This study aims to determine whether there was a relationship between maternal characteristics, husband support and the role of midwives with the participation of mothers following the class of pregnant women. The location of the research was conducted at Puskesmas Guguak Panjang with 74 samples. Data analysis included univariate, bivariate and multivariate analysis.The results of the bivariate analysis showed that there was no correlation between maternal characteristics with maternal participation in maternal class while emotional support, instrumental support, information support and assessment support (p = 0.0001) had a relationship with maternal participation in the class of pregnant women. The role of external midwives (p = 0.002), the role of internal midwives (p = 0.001) related to maternal participation in the mother's class. Multivariate results show the role of internal midwives that greatly influences the participation of mothers who attend classes for pregnant women (p = 0.001).The role of midwives and husband support greatly affects the participation of mothers following the class of pregnant women.